Level of knowledge, attitude, perceived behavior control, subjective norm and behavior of household solid waste towards zero waste management among Malaysian consumer - M. J., Zuroni; O., Syuhaily; M. A., Afida Mastura; M. S., Roslina; A. K., Nurul Aini (World Academy of Science, Engineering and Technology (W A S E T), 2018)
The impact of country development has caused an increase of solid waste. The increase in population causes ofexcess usage thus effecting the sustainable environment. Zero waste management involves maximizing practices of recyclingand minimizing residual waste. This paper seeks to analyze the relationship between knowledge, attitude, perceived behaviorcontrol, subjective norm and behavior of household solid waste towards household solid waste management among urbanhouseholds in 8 states that have been implemented and enforced regulations under the Solid Waste Management and PublicCleansing Act 2007 (Act 672) in Malaysia. A total of respondents are 605 and we used a purposive sampling for location andsimple sampling for sample size. Data collected by using self-administered questionnaire and were analyzed using SPSSsoftware. The Pearson Correlation Test is to examine the relationship between four variables. Results show that knowledgescores are high because they have an awareness of the importance of managing solid waste. For attitude, perceived behaviorcontrol, subjective norm and behavioral scores at a moderate level in solid waste management activities. The findings showthat there is a significant relationship between knowledge and behavior of household solid waste (r = 0.136 **, p = 0.001),there is a significant relationship between attitude and behavior (r = 0.238 **, p = 0.000), there is a significant relationshipbetween perceived behavior control and behavior (r = 0.516 **, p = 0.000) and there is a significant relationship betweensubjective norm and behavior (r = 0.494 **, p = 0.000). The conclusion is that there is a relationship between knowledge,attitude, perceived behavior control and subjective norm toward the behavior of household solid waste management.Therefore, in the findings of the study, all parties including the government should work together to enhance the knowledge,attitude, perceived behavior control and behavior of household solid waste management in other states that have notimplemented and enforced regulations under the Solid Waste and Public Cleansing Management Act 2007 (Act 672).